Aspects of change in the Canadian federal public service - McIntosh, Norm (1997)
This article is divided into two parts. The first part looks at some significant changes that have taken place in Canada's federal public service over the last two or three years. These changes include the introduction of new management techniques, new organizational structures and new approaches to governance. The second part deals with my own organization, consulting and audit Canada, including the rationale for our existence, the kind of work we do and the issues we face. Both parts raise issues that are pertinent to the subject of public sector versus private sector, in the context of service delivery. - Reproduced
Keywords: Civil service - Canada; Administrative reform